Robot or human? Manoeuvring switching intention after robot service failure - Wing Han Helen Lee; Suk Ha Grace Chan; Binglin Martin Tang; Zhiwen Song (PLoS ONE, 2025)
This study attempts to scrutinise tourists’ switching intentions towards human service after a robot service failure, with the zone of tolerance and trust on stance in technology as moderators. The study adopts the unified theory of acceptance and use of technology as a conceptual framework. Quantitative approach through is adopted. Specifically, the retrospective survey is designed to recall robot-service failures,” A total of 330 valid samples were collected and structural equation modelling was employed for data analysis. The findings revealed an insignificant direct effect of tourists’ switching intentions towards human services after a robot service failure. The findings validate the moderating effects of the zone of tolerance and trust stance on technology on tourists’ customer (dis)satisfaction in terms of severity and controllability while denying the reliability aspect. This study fills the literature gap by elucidating paradoxical switching intention and conceptualising work on human–robot behavioural intentions. The study provides theoretical and practical contributions, with limitations and recommendations for future research directions.